Monkeypox Virus Infection across 16 Countries — April–June 2022 - John Thornhill; Andrea Antinori; Chloe Orkin (2022)
To the Editor: According to Thornhill et al. (Aug.25 issue), 1 semen was positive for monkeypox (recently renamed mpox) virus on polymerase-chain-reaction testing in 29 persons.Did the authors analyze prostatic fluid?Semen is not homogeneous and results from at least four exocrine organs and four mucosal exocrine glands.The majority of human immunodeficiency virus (HIV) in semen originates distal to the vas deferens. 2The importance of the prostate reservoir for HIV was shown by Smith et al., who found undetectable seminal plasma HIV RNA in all semen samples obtained without prostatic massage but detectable seminal plasma HIV RNA (≥25 copies per milliliter) in at least one sample obtained after prostatic massage. 3Detailed localization studies of mpox virus are important because the prostate may serve as a reservoir and mpox virus may arise from local replication in the male genitourinary subcompartments.Second, did the authors observe Trichomonas vaginalis in any of the persons infected with mpox virus?Although T. vaginalis infection is not necessarily a reportable condition, it has been implicated in the pathogenesis of persistent urethritis and prostatitis owing to the postulated phagocytosis and potential killing of Neisseria gonorrhoeae. 4T. vaginalis may be an important endocytobiotic agent in the transmission and potential persistence of mpox virus infection in the genitourinary tract.